Migration and foraging strategies at varying spatial scales in western North Atlantic right whales: a review of hypotheses - Kenney, Robert D.; Mayo, Charles A.; Winn, Howard E. (J. Cetacean Res. Manage., 2020)
Western North Atlantic right whales (Eubalaena glacialis) utilise several important foraging habitats off the northeastern United States and eastern Canada, where they feed on dense patches of zooplankton. At a fundamental level, a right whale’s optimal strategy should be to locate and exploit the prey patches with the highest net energetic return from foraging. There remain many questions, however, concerning their migration and foraging strategies and the environmental cues and sensory modalities involved in migration and foraging, all of which are likely to vary at different spatial scales. For example, a right whale most likely uses different mechanisms and strategies for location of primary feeding grounds than those used for detection of optimum prey patches within a feeding area. This paper proposes a multi-scaled, hierarchical, conceptual model of right whale migratory and foraging strategies and presents a variety of hypotheses concerning the mechanisms involved. Right whales may return to the general area of their feeding grounds based on prior experience. The locations of successful foraging in the immediately preceding years are likely to be re-visited, as are habitats to which an animal was exposed while accompanying its mother during its first year of life. It is also possible that the whales utilise large- or medium-scale environmental cues, such as currents, temperature discontinuities, or salinity signals indicating coastal plumes, to locate likely areas of high zooplankton patch density. Whilst on their feeding grounds, right whales tend to be aggregated, but there are usually outliers which may represent occasional excursions in search of other prey patches, though there is currently no evidence to address whether they communicate information about prey to other individuals. Their behaviour whilst actively feeding indicates that they can detect differences in patch density and adjust their behaviour accordingly. A likely sensory mechanism for quantification of patch density and triggering of feeding behaviour would be the vibrissae around the anterior opening of the mouth.